2008
DOI: 10.1007/s00213-008-1428-9
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of 5-HTTLPR genotypes on mood, memory, and attention bias following acute tryptophan depletion and stress exposure

Abstract: Rationale Polymorphisms of the serotonin transporter gene (5-HTTLPR) may be associated with increased vulnerability to acute tryptophan depletion (ATD) and depression vulnerability especially following stressful life events. Objective The aim of the present study was to investigate the effects of ATD in subjects with different 5-HTTLPR profiles before and after stress exposure on affective and cognitive-attentional changes. Materials and methods Eighteen subjects with homozygotic short alleles (S′/S′) and 17 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 83 publications
(102 reference statements)
0
12
0
Order By: Relevance
“…Four studies reported a main effect of the 5-HTTLPR genotype (Gotlib et al 2008;Dougherty et al 2010;Mueller et al 2010;Way and Taylor 2010), whereas four studies did not find a main effect of the same genotype (Alexander et al 2009;Firk and Markus 2009;Markus and Firk 2009;Wust et al 2009). These conflicting results might be explained by methodological differences between the studies, such as inconsistencies in the nature of the stress task, the use of different study populations, and discrepancies in the timing of salivary cortisol sampling.…”
Section: -Httlpr Acute Stress and Neuroticismmentioning
confidence: 77%
“…Four studies reported a main effect of the 5-HTTLPR genotype (Gotlib et al 2008;Dougherty et al 2010;Mueller et al 2010;Way and Taylor 2010), whereas four studies did not find a main effect of the same genotype (Alexander et al 2009;Firk and Markus 2009;Markus and Firk 2009;Wust et al 2009). These conflicting results might be explained by methodological differences between the studies, such as inconsistencies in the nature of the stress task, the use of different study populations, and discrepancies in the timing of salivary cortisol sampling.…”
Section: -Httlpr Acute Stress and Neuroticismmentioning
confidence: 77%
“…We can therefore definitively say that there is no evidence for cognitive effects of 5HTTLPR on these measures of working memory, response inhibition, or IQ in healthy children. It remains plausible, however, that genetic effects on cognition are seen in circumstances in which the serotonergic status quo has been disrupted, for example, by stress, tryptophan depletion [Roiser et al, 2007; Firk and Markus, 2009[ or in neuropsychiatric disorders [Beevers et al, 2007; da Rocha et al, 2008[. Some apparently conflicting results may therefore have arisen because cognitive differences between genotypes appear exaggerated in circumstances of serotonergic perturbation, where normal mechanisms of compensation for genetic variation are disturbed.…”
Section: Discussionmentioning
confidence: 99%
“…MAOA genotype has been reported to significantly affect IQ among healthy Chinese women [Yu et al, 2005[ and children with autism [Yirmiya et al, 2002; Cohen et al, 2003[ but with conflicting directions of effect. Reports regarding cognitive effects of the 5HTTLPR polymorphism have been predominantly negative for standard neuropsychological measures such as IQ, response inhibition, and sustained attention [Fallgatter et al, 1999; Clark et al, 2005; Payton et al, 2005; Roiser et al, 2007; Strobel et al, 2007; da Rocha et al, 2008; Borg et al, 2009[, though there are now multiple reports of associations with risk-taking, decision-making, and attentional biases [Beevers et al, 2007; Homberg et al, 2008; da Rocha et al, 2008; Crisan et al, 2009; Firk and Markus, 2009; Fox et al, 2009; Roiser et al, 2009[.…”
Section: Introductionmentioning
confidence: 99%
“…A study performed on healthy women exposed to tryptophan depletion showed reduction in mood compared to controls, but this effect was shown to be moderated by genotype in the 5HTTLPR. A stress-inducing task caused a significant increase in depressive symptoms and reduced sense of vigour among carriers of the low-functioning variant of 5HTTLPR in response to tryptophan depletion, whereas the opposite effect was observed for carriers of the high-functioning variant (70). These results are in line with the observations that the low-functioning variant of 5HTTLPR has been associated with increased amygdala reactivity and reduced stress-coping (71).…”
Section: The Effect Of Serotonin In Adulthoodmentioning
confidence: 93%